Efficient sewage treatment agent and preparation method thereof

Through the synergistic effect of CaWO4/ZIF-67 composite material with Al2(SO4)3 and MnO2, a high-efficiency sewage treatment agent was prepared, which solved the problems of low treatment efficiency, high cost and secondary pollution of existing sewage treatment agents, and achieved It has fast adsorption and good stability of sewage purification effects.

CN119263444AActive Publication Date: 2025-01-07SHAANXI NEW JINSHENG TECHNOLOGY DEVELOPMENT CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411736416.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-01-07
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

Existing sewage treatment agents are inefficient, costly and may cause secondary pollution, difficult to meet reuse or emission standards, and pose a potential threat to the environment and human health.

Method used

Using CaWO4/ZIF-67 composite material combined with the flocculation of Al2(SO4)3 and the catalytic action of MnO2, Fe3O4 is added to impart magnetism, and high-efficiency wastewater treatment agent is prepared through ultrasonic treatment and hydrothermal reaction, and the high porosity of ZIF-67 and Microporous rapidly adsorb heavy metal ions and reduces the COD of wastewater through the synergistic action of Al2(SO4)3 and NaHSO3.

Benefits of technology

It has achieved efficient removal of heavy metal ions and organic pollutants in water, with good stability, can be separated by magnetic field and recycled multiple times, reducing the cost of sewage treatment, avoiding secondary pollution, and meeting the environmental protection and economic needs of sewage treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263444A_ABST
    Figure CN119263444A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sewage treatment, and particularly relates to an efficient sewage treatment agent and a preparation method thereof, and the efficient sewage treatment agent comprises the following components in parts by weight: 20-30 parts of a CaWO4 / ZIF-67 composite material, 10-20 parts of Al2 (SO4) 3, 5-10 parts of Fe2O3, 0.5-2 parts of NaHSO3, 1-5 parts of Na2SiO3 and 3-15 parts of MnO2. The ZIF-67 has high adsorption efficiency due to high porosity and adjustable characteristics, the ZIF-67 and the CaWO4 are compounded, and the composite material is endowed with magnetism, so that the composite material can quickly adsorb pollutants to the surface, the problems that the single ZIF-67 is easy to agglomerate and difficult to recycle are solved, the flocculation effect and the reduction effect are combined, the COD (Chemical Oxygen Demand) of sewage is further reduced, and the sewage treatment efficiency is improved. The effect of efficiently purifying the sewage is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sewage treatment, and specifically relates to a high-efficiency sewage treatment agent and a preparation method thereof. Background Art

[0002] Water pollution is a rapidly growing environmental problem that requires effective management methods. Sewage contains a wide variety of pollutants that can accumulate and remain in the environment for a long time, are potentially harmful to the environment, and are difficult to treat, so effective sewage treatment methods are needed to remove or reduce their concentrations.

[0003] Although the existing sewage treatment technology can remove pollutants in sewage to a certain extent, there are still the following problems: low treatment efficiency: some traditional sewage treatment agents have low removal rates for pollutants such as COD (chemical oxygen demand), BOD (biochemical oxygen demand), and suspended solids, resulting in the water quality after treatment being difficult to meet the reuse or discharge standards; high cost: some high-efficiency sewage treatment agents have high costs, which limits their application in actual projects; secondary pollution problems: some sewage treatment agents may produce toxic and harmful by-products during use, posing a potential threat to the environment and human health. Therefore, it is necessary to research and develop a sewage treatment agent that is efficient, environmentally friendly, low-cost, and easy to operate, to provide a new and efficient solution for the sewage treatment field. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present invention proposes a high-efficiency sewage treatment agent and a preparation method thereof. The high-efficiency sewage treatment agent prepared by the present invention adopts a CaWO4 / ZIF-67 composite material, combined with the strong flocculation effect of Al2(SO4)3 and the catalytic effect of MnO2. ZIF-67 has a high adsorption efficiency due to its high porosity and adjustable characteristics. The inherent microporosity of ZIF-67 enables heavy metal ions to diffuse into the framework efficiently and quickly. ZIF-67 is compounded with CaWO4, and Fe3O4 is added during the synthesis process to give the composite material magnetism, so that the composite material can quickly adsorb heavy metal ions to the surface. After CaWO4 is compounded with ZIF-67, the characteristics of ZIF-67 being easy to agglomerate, difficult to use and recycle are solved, and the surface active substances are increased, the adsorption performance is increased, and the COD of sewage is further reduced by combining the flocculation effect of Al2(SO4)3 and the reduction effect of NaHSO3. The high-efficiency sewage treatment agent prepared by the present invention has good flocculation and adsorption capabilities, can quickly adsorb pollutants, has good stability, can be easily separated by a magnetic field, can be recycled multiple times, and has good economic practicality.

[0005] In order to achieve the above technical objectives, the technical solutions adopted by the present invention are as follows: The invention provides a high-efficiency sewage treatment agent, which is composed of the following raw materials in parts by weight: 20-30 parts of CaWO4 / ZIF-67 composite material, 10-20 parts of Al2(SO4)3, 5-10 parts of Fe2O3, 1-5 parts of Na2SiO3, 0.5-2 parts of NaHSO3, and 3-15 parts of MnO2; Furthermore, the raw materials for preparing the CaWO4 / ZIF-67 composite material are: Ca(NO3)2·4H2O, Na2WO4·2H2O, Co(NO3)2·6H2O, CTAB (hexadecyltrimethylammonium bromide), C4H6N2 (2-methylimidazole) and Fe3O4; The preparation method of the CaWO4 / ZIF-67 composite material specifically comprises the following steps: S1, weigh Ca(NO3)2·4H2O and dissolve it in ethylene glycol to form a first solution, weigh Na2WO4·2H2O and dissolve it in deionized water to form a second solution, then slowly pour the second solution into the first solution, put it in a magnetic stirrer and stir it at a speed of 180-300 rpm at a temperature of 70 °C to form a mixture; S2, subjecting the mixture obtained in step S1 to a hydrothermal reaction at a reaction temperature of 180°C and a reaction time of 24 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a white precipitate. The white precipitate is washed alternately with ethanol and deionized water for 3 times, dried in an oven at 70°C for 12 hours, and taken out and ground to obtain CaWO4; S3, add CTAB and Co(NO3)2·6H2O to deionized water, and ultrasonicate at 240 W for 15 min to form a uniform solution A, add C4H6N2 and Fe3O4 to anhydrous ethanol to obtain solution B, slowly pour solution A into solution B, mix well, and form a mixed solution; S4, adding the CaWO4 prepared in step S2 to the mixed solution, mixing by ultrasonication, drying to obtain a composite material precursor, and then calcining at 400°C for 4-6 h to obtain a CaWO4 / ZIF-67 composite material.

[0006] Furthermore, the dosage ratio of Ca(NO3)2·4H2O to ethylene glycol is 0.1 g:7 mL, the dosage ratio of Na2WO4·2H2O to deionized water is 0.1 g:15 mL, the molar ratio of Ca(NO3)2·4H2O to Na2WO4·2H2O is 1:1, and the volume ratio of solution A to solution B is 1:12.

[0007] Furthermore, the dosage ratio of CATB, Co(NO3)2·6H2O and deionized water is 1 mg:0.15 g:2.5 mL, and the dosage ratio of C4H6N2, Fe3O4 and anhydrous ethanol is 1 g:0.5 g:10 mL.

[0008] Furthermore, the dosage ratio of CaWO4 to the mixed solution is 0.1-0.5 g:25 mL.

[0009] The present invention also provides a method for preparing a high-efficiency sewage treatment agent, which specifically comprises the following steps: Y1, weigh Al2(SO4)3 and Fe2O3 by weight, dissolve them in deionized water, and stir at 200-500 rpm to form a mixed solution; Y2, weighing CaWO4 / ZIF-67 composite material and NaHSO3 by weight, adding them to the mixed solution obtained in step Y1, and mixing them at 70-90°C and 200 rpm with magnetic stirring to form a suspension; Y3. Add Na2SiO3 and MnO2 to the suspension obtained in step Y2, stir and mix at 300 rpm, let stand for 30-60 minutes, then centrifuge and dry to obtain a high-efficiency sewage treatment agent.

[0010] Compared with the prior art, the present invention has the following beneficial effects: The high-efficiency sewage treatment agent prepared by the present invention adopts CaWO4 / ZIF-67 composite material, combined with the strong flocculation effect of Al2(SO4)3 and the catalytic effect of MnO2, so that the prepared sewage treatment agent has the characteristics of high efficiency, stability, environmental protection, etc. ZIF-67 has high adsorption efficiency due to its high porosity and adjustable characteristics, and can effectively remove heavy metal ions and organic pollutants in water. The inherent microporosity of ZIF-67 enables heavy metal ions to diffuse into the framework efficiently and quickly. ZIF-67 is compounded with calcium tungstate, and Fe3O4 is added during the synthesis process to give the composite material magnetism, so that the magnetic composite material can adsorb heavy metal ions such as Pb 2+ Cr 6+Plasma and organic dyes are rapidly adsorbed to the surface, then enter the interior of the material and combine with the active center of the CaWO4 / ZIF-67 composite material until adsorption saturation is reached. After CaWO4 is compounded with ZIF-67, the characteristics of ZIF-67 that it is easy to agglomerate, difficult to use and recycle are solved, and the surface active substances are increased, and the adsorption performance is improved, so that the adsorption mechanism of the CaWO4 / ZIF-67 composite material is attributed to electrostatic attraction and surface complexation of oxygen-containing functional groups, rather than relying solely on the interaction of CN in ZIF-67, which greatly enhances the purification effect of sewage; CaWO4 has good chemical stability and can remain stable under different pH values ​​and chemical environments. The combination of ZIF-67 and CaWO4 improves the overall stability of the composite material. At the same time, the composite material is magnetic and can be easily separated by a magnetic field, solving the problem that traditional powdered functional materials are difficult to recycle, thereby avoiding secondary pollution. Al2(SO4)3 is hydrolyzed in water to form aluminum hydroxide colloid, which has good flocculation effect. It is combined with the flocculation and adsorption of Fe2O3, and assisted by Na2SiO3 to promote the formation of flocs of suspended particles in sewage, accelerating the aggregation and sedimentation of suspended matter and colloidal particles in water; Al2(SO4)3 can adjust the pH value of water, and Na2SiO3 is partially hydrolyzed into silicic acid and sodium hydroxide in sewage, which assists Al2(SO4)3 in regulating the pH of sewage and jointly maintains the stability of the pH of water. The catalytic oxidation of MnO2 helps to decompose organic pollutants in water, and calcium tungstate / ZIF-67 can adsorb these decomposition products and heavy metal ions to achieve comprehensive removal of pollutants. The catalysis of MnO2 accelerates the efficient adsorption and separation of pollutants by CaWO4 / ZIF-67, thereby improving the efficiency of sewage treatment. The CaWO4 / ZIF-67 composite material provides mechanical support for MnO2, protecting it from wear during sewage treatment and maintaining its catalytic activity. The magnetism of Fe2O3 helps to recycle MnO2 and Al2(SO4)3, and prevents their loss during water treatment. NaHSO3 has a sterilizing and disinfecting effect on sewage, can reduce oxidative pollutants in sewage, reduce the chroma and COD of sewage, and further purify the sewage. The high-efficiency sewage treatment agent prepared by the present invention has good flocculation and adsorption capacity, can quickly adsorb pollutants, has good stability, can be easily separated by magnetic field, can be recycled multiple times, has low preparation cost, and will not cause secondary pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 Schematic diagram of heavy metal ion removal rate and BOD removal rate of the high-efficiency sewage treatment agent prepared in Examples 1-3 of the present invention and Comparative Examples 1-3; Figure 2 A schematic diagram of the adsorption amount of the high-efficiency sewage treatment agent prepared in Example 1 of the present invention and Comparative Examples 1-3 over time; Figure 3 Schematic diagram of the stability of the high-efficiency sewage treatment agents prepared in Examples 1-3 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION

[0012] In order to make the technical solution of the present invention better understood by the technical personnel in the field, and to make the above-mentioned features, purposes and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with the embodiments. The embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0013] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0014] Example 1: This example provides a high-efficiency sewage treatment agent, which is composed of the following raw materials in parts by weight: 20 parts of CaWO4 / ZIF-67 composite material, 20 parts of Al2(SO4)3, 5 parts of Fe2O3, 1 part of Na2SiO3, 0.5 parts of NaHSO3, and 3 parts of MnO2; The preparation method of the CaWO4 / ZIF-67 composite material specifically comprises the following steps: S1, weigh Ca(NO3)2·4H2O and dissolve it in ethylene glycol, the amount ratio of Ca(NO3)2·4H2O to ethylene glycol is 0.1 g:7 mL, to form a first solution, weigh Na2WO4·2H2O and dissolve it in deionized water, the amount ratio of Na2WO4·2H2O to deionized water is 0.1 g:15 mL, to form a second solution, the molar ratio of Ca(NO3)2·4H2O to Na2WO4·2H2O is 1:1, then, slowly pour the second solution into the first solution, put it in a magnetic stirrer and stir it at a speed of 180 rpm at a temperature of 70°C to form a mixture; S2, transfer the mixture obtained in step S1 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a reaction temperature of 180 °C and a reaction time of 24 h. After the reaction is completed, cool to room temperature to obtain a white precipitate. Wash the obtained white precipitate with ethanol and deionized water alternately for 3 times, dry it in an oven at 70 °C for 12 h, take it out and grind it to obtain CaWO4; S3, CTAB and Co(NO3)2·6H2O were added to deionized water, the dosage ratio of CATB, Co(NO3)2·6H2O and deionized water was 1 mg:0.15 g:2.5 mL, and ultrasonic treatment was performed at 240 W for 15 min to form a uniform solution A, C4H6N2 and Fe3O4 were added to anhydrous ethanol to obtain solution B, the dosage ratio of C4H6N2, Fe3O4 and anhydrous ethanol was 1 g:0.5 g:10 mL, solution A was slowly poured into solution B, mixed evenly, and a mixed solution was formed; S4, adding CaWO4 prepared in step S2 to the mixed solution obtained in step S3, the amount ratio of CaWO4 to the mixed solution is 0.1 g:25 mL, treating with an ultrasonic cleaner at 240 W for 30 min to mix, drying to obtain a composite material precursor, and then calcining at 400 ° C for 4 h to obtain a CaWO4 / ZIF-67 composite material.

[0015] This embodiment also provides a method for preparing a high-efficiency sewage treatment agent, which specifically comprises the following steps: Y1, weigh 20 parts of Al2(SO4)3 and 5 parts of Fe2O3, dissolve them in deionized water, and stir at 200 rpm to form a mixed solution; Y2, weigh 20 parts of CaWO4 / ZIF-67 composite material and 0.5 parts of NaHSO3, add them to the mixed solution obtained in step Y1, and mix them at 70°C and 200 rpm with magnetic stirring to form a suspension; Y3. Add 1 part of Na2SiO3 and 3 parts of MnO2 to the suspension obtained in step Y2, stir and mix at 300 rpm, let stand for 30 min, then centrifuge and dry to obtain a high-efficiency sewage treatment agent.

[0016] Example 2: This example provides a high-efficiency sewage treatment agent, which is composed of the following raw materials in parts by weight: 25 parts of CaWO4 / ZIF-67 composite material, 15 parts of Al2(SO4)3, 8 parts of Fe2O3, 3 parts of Na2SiO3, 1.2 parts of NaHSO3, and 9 parts of MnO2; The preparation method of the CaWO4 / ZIF-67 composite material specifically comprises the following steps: S1, weigh Ca(NO3)2·4H2O and dissolve it in ethylene glycol, the amount ratio of Ca(NO3)2·4H2O to ethylene glycol is 0.1 g:7 mL, to form a first solution, weigh Na2WO4·2H2O and dissolve it in deionized water, the amount ratio of Na2WO4·2H2O to deionized water is 0.1 g:15 mL, to form a second solution, the molar ratio of Ca(NO3)2·4H2O to Na2WO4·2H2O is 1:1, then, slowly pour the second solution into the first solution, put it in a magnetic stirrer and stir it at a speed of 240 rpm at a temperature of 70°C to form a mixture; S2, transfer the mixture obtained in step S1 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a reaction temperature of 180 °C and a reaction time of 24 h. After the reaction is completed, cool to room temperature to obtain a white precipitate. Wash the obtained white precipitate with ethanol and deionized water alternately for 3 times, dry it in an oven at 70 °C for 12 h, take it out and grind it to obtain CaWO4; S3, CTAB and Co(NO3)2·6H2O were added to deionized water, the dosage ratio of CATB, Co(NO3)2·6H2O and deionized water was 1 mg:0.15 g:2.5 mL, and ultrasonic treatment was performed at 240 W for 15 min to form a uniform solution A, C4H6N2 and Fe3O4 were added to anhydrous ethanol to obtain solution B, the dosage ratio of C4H6N2, Fe3O4 and anhydrous ethanol was 1 g:0.5 g:10 mL, solution A was slowly poured into solution B, mixed evenly, and a mixed solution was formed; S4, adding CaWO4 prepared in step S2 to the mixed solution obtained in step S3, the amount ratio of CaWO4 to the mixed solution is 0.3 g:25 mL, treating with an ultrasonic cleaner at 240 W for 30 min to mix, drying to obtain a composite material precursor, and then calcining at 400 ° C for 5 h to obtain a CaWO4 / ZIF-67 composite material.

[0017] This embodiment also provides a method for preparing a high-efficiency sewage treatment agent, which specifically comprises the following steps: Y1, weigh 15 parts of Al2(SO4)3 and 8 parts of Fe2O3, dissolve them in deionized water, and stir at 400 rpm to form a mixed solution; Y2, weigh 25 parts of CaWO4 / ZIF-67 composite material and 1.2 parts of NaHSO3, add them to the mixed solution obtained in step Y1, and mix them at 80°C and 200 rpm with magnetic stirring to form a suspension; Y3. Add 3 parts of Na2SiO3 and 9 parts of MnO2 to the suspension obtained in step Y2, stir and mix at 300 rpm, let stand for 45 minutes, then centrifuge and dry to obtain a high-efficiency sewage treatment agent.

[0018] Example 3: This example provides a high-efficiency sewage treatment agent, which is composed of the following raw materials in parts by weight: 30 parts of CaWO4 / ZIF-67 composite material, 10 parts of Al2(SO4)3, 10 parts of Fe2O3, 5 parts of Na2SiO3, 2 parts of NaHSO3, and 15 parts of MnO2; The preparation method of the CaWO4 / ZIF-67 composite material specifically comprises the following steps: S1, weigh Ca(NO3)2·4H2O and dissolve it in ethylene glycol, the amount ratio of Ca(NO3)2·4H2O to ethylene glycol is 0.1 g:7 mL, to form a first solution, weigh Na2WO4·2H2O and dissolve it in deionized water, the amount ratio of Na2WO4·2H2O to deionized water is 0.1 g:15 mL, to form a second solution, the molar ratio of Ca(NO3)2·4H2O to Na2WO4·2H2O is 1:1, then, slowly pour the second solution into the first solution, put it in a magnetic stirrer and stir it at a speed of 300 rpm at a temperature of 70°C to form a mixture; S2, transfer the mixture obtained in step S1 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a reaction temperature of 180 °C and a reaction time of 24 h. After the reaction is completed, cool to room temperature to obtain a white precipitate. Wash the obtained white precipitate with ethanol and deionized water alternately for 3 times, dry it in an oven at 70 °C for 12 h, take it out and grind it to obtain CaWO4; S3, CTAB and Co(NO3)2·6H2O were added to deionized water, the dosage ratio of CATB, Co(NO3)2·6H2O and deionized water was 1 mg:0.15 g:2.5 mL, and ultrasonic treatment was performed at 240 W for 15 min to form a uniform solution A, C4H6N2 and Fe3O4 were added to anhydrous ethanol to obtain solution B, the dosage ratio of C4H6N2, Fe3O4 and anhydrous ethanol was 1 mg:0.15 g:2.5 mL, solution A was slowly poured into solution B, mixed evenly, and a mixed solution was formed; S4, adding CaWO4 prepared in step S2 to the mixed solution obtained in step S3, the amount ratio of CaWO4 to the mixed solution is 0.5 g:25 mL, treating with an ultrasonic cleaner at 240 W for 30 min to mix, drying to obtain a composite material precursor, and then calcining at 400 ° C for 4-6 h to obtain a CaWO4 / ZIF-67 composite material.

[0019] This embodiment also provides a method for preparing a high-efficiency sewage treatment agent, which specifically comprises the following steps: Y1, weigh 10 parts of Al2(SO4)3 and 10 parts of Fe2O3, dissolve them in deionized water, and stir at 500 rpm to form a mixed solution; Y2, weigh 30 parts of CaWO4 / ZIF-67 composite material and 2 parts of NaHSO3, add them to the mixed solution obtained in step Y1, and mix them at 90°C and 200 rpm with magnetic stirring to form a suspension; Y3. Add 5 parts of Na2SiO3 and 15 parts of MnO2 to the suspension obtained in step Y2, stir and mix at 300 rpm, let stand for 60 min, then centrifuge and dry to obtain a high-efficiency sewage treatment agent.

[0020] The difference between Comparative Example 1 and Example 1 is that no CaWO4 / ZIF-67 composite material is added, and the rest is the same as Example 1.

[0021] The difference between Comparative Example 2 and Example 1 is that Al2(SO4)3 is not added, and the rest is the same as Example 1.

[0022] The difference between Comparative Example 3 and Example 1 is that no MnO2 is added, and the rest is the same as Example 1.

[0023] Experimental Example Industrial wastewater discharged from the same batch was divided into 6 groups for testing, namely Examples 1-3 and Comparative Examples 1-3, with a dosage of 0.2 g / L, and the COD removal rate, suspended solids removal rate and ammonia nitrogen removal rate of the high-efficiency sewage treatment agent prepared by the present invention were determined.

[0024] Experimental Example 1: The chemical oxygen demand (COD) content in sewage was determined using the national standard GB11914-89 "COD determination dichromate method". 20 mL of each group was taken and placed in a glass bottle for testing. 10.0 mL of potassium dichromate standard solution and several explosion-proof glass beads were added to each group of samples and shaken well. Connect the conical flask to the lower end of the condenser of the reflux device and connect the condensed water. Slowly add 30 mL of silver sulfate-sulfuric acid reagent from the upper end of the condenser to prevent the escape of low-boiling organic matter, and constantly rotate the conical flask to mix it evenly. Reflux for two hours from the beginning of the boiling of the solution. After cooling, rinse the condenser from the upper end of the condenser with 20-30 mL of water, remove the conical flask, and dilute it with water to about 140 mL. After the solution is cooled to room temperature, add 3 drops of 1,10-phenanthroline indicator solution and titrate with ammonium ferrous sulfate standard titration solution. The end point is when the color of the solution changes from yellow to blue-green to reddish brown. Record the consumption of milliliters of ammonium ferrous sulfate standard titration solution V2. The chemical oxygen demand of the water sample in mg / L is calculated as follows: COD (mg / L) = c × (V1-V2) × 8000 / V0 Where: C is the concentration of ammonium ferrous sulfate standard titration solution (4.6), mol / L; V1 is the volume of ammonium ferrous sulfate standard titration solution consumed in the blank test, mL; V2 is the volume of ammonium ferrous sulfate standard titration solution consumed in the sample determination, mL; V0 is the volume of the sample, mL; 8000 is the conversion value of 1 / 4 the molar mass of O2 in mg / L. The COD removal rate is calculated based on the calculated chemical oxygen demand, and the results are recorded in Table 1.

[0025] Experimental Example 2: Suspended solids were determined according to the weight method specified in the national standard GB11901-89. The test steps are as follows: (1) Preparation of the filter membrane Place the filter membrane in a weighing bottle and place it in an oven at 105 °C for drying. After drying for half an hour, place the filter membrane in a dryer and weigh the filter membrane after cooling to room temperature. Repeat the above steps until the difference between the two weighings of the filter membrane is less than 0.2 mg. Place the filter membrane on the filter tray, moisten the filter membrane with distilled water, and continue to filter. (2) Determination of suspended solids Filter 100 mL of the thoroughly shaken water sample to allow all the water to pass through the filter membrane. Wash the filter membrane with distilled water, 10 mL each time, three times, and continue to filter to remove excess water. After the filtration stops, place the filter membrane carrying the suspended solids in the original weighing bottle, then dry it in an oven at 105 °C for one hour, then place it in a dryer to cool, and weigh the total weight of the filter membrane, suspended solids, and weighing bottle. Repeat the steps in (2) until the difference between the two total weights is less than 0.4 mg. The content of suspended matter is calculated according to the following formula: C = (AB) × 10 4 / V, where C is the concentration of suspended solids in water, in mg / L; A is the total weight of the filter membrane, suspended solids and weighing bottle, in g; E is the weight of the filter membrane and weighing bottle, in g; V6 is the volume of the water sample, in mL. The removal rate of suspended solids is calculated based on the results and the results are recorded in Table 1.

[0026] Experimental Example 3: According to the Nessler reagent colorimetric method specified in the national standard GB-T 7479-1987, the ammonia nitrogen content in sewage was determined. 0, 0.50, 1.00, 2.00, 6.00, 8.00, and 10.00 mL of 10 mg / L ammonia nitrogen standard solution were accurately pipetted with a pipette, 1.00 mL of KNaC4H4O6 solution and 1.5 mL of Nessler reagent were added, and the volume was made up to 50 mL with ultrapure water. The mixture was mixed evenly, allowed to stand for 10 min, and heated at 420 °C. The absorbance was measured at nm, with ultrapure water as the blank sample. The difference between the actual absorbance in the water sample and the blank sample was used to obtain the ammonia nitrogen mass (mg) from the calibration standard curve. The ammonia nitrogen content was calculated using the following formula: ammonia nitrogen (NH3-N, mg / L) = m / V×1000, where: m is the ammonia nitrogen compound content on the calibration standard curve, mg; V is the test water sample volume, mL. The ammonia nitrogen removal rate was calculated by measuring the ammonia nitrogen content, and the calculation results are recorded in Table 1.

[0027] Table 1

[0028] The results in Table 1 show that the COD removal rates of Examples 1-3 of the present invention are significantly higher than those of the comparative example, indicating that the present invention successfully prepares a high-efficiency sewage treatment agent, and the removal rate of suspended solids reaches 99.5%, indicating that the sewage treatment agent can quickly separate suspended solids from sewage. From the removal results of ammonia nitrogen, the high-efficiency sewage treatment agent prepared by the present invention can effectively remove ammonia nitrogen and purify sewage, indicating that the sewage treatment agent prepared by the present invention has a good sewage evolution effect through the interaction between materials.

[0029] Figure 1 The results show that the high-efficiency sewage treatment agent prepared by the present invention has a removal rate of 99.6% for heavy metal ions and a BOD removal rate of 95.8%, indicating that the sewage treatment agent prepared by the present invention has a good function of removing heavy metal ions in sewage. Figure 2 It is shown that adsorption saturation is reached at nearly 60 minutes, indicating that the sewage treatment agent prepared by the present invention can quickly adsorb pollutants in water and purify sewage; Figure 3 The high-efficiency sewage treatment agent prepared by the present invention has a heavy metal removal rate of 93.2% after 5 repeated experiments, indicating that the sewage treatment agent prepared by the present invention has good stability and can be reused many times.

[0030] In summary, through the verification of the embodiments and comparative examples, it can be known that the present invention increases the active substances, improves the adsorption efficiency, and improves the overall stability through the compounding of CaWO4 and ZIF-67. At the same time, combined with the strong flocculation effect of Al2(SO4)3 and Fe2O3, the suspended matter in the sewage can be quickly settled and separated, and MnO2 helps to catalyze the composite material and accelerate the adsorption efficiency. The CaWO4 / ZIF-67 composite material provides mechanical support for MnO2 to protect it from continuing to play a role in the sewage treatment process. The high-efficiency sewage treatment agent prepared by the present invention has good flocculation and adsorption capacity, can quickly adsorb pollutants, has good stability, and has potential promotion value in the treatment of domestic sewage, industrial wastewater, etc.

[0031] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A high-efficiency sewage treatment agent, characterized in that: The high-efficiency sewage treatment agent is composed of the following raw materials in parts by weight: 20-30 parts of CaWO4 / ZIF-67 composite material, 10-20 parts of Al2(SO4)3, 5-10 parts of Fe2O3, 1-5 parts of Na2SiO3, 0.5-2 parts of NaHSO3, and 3-15 parts of MnO2; The raw materials for preparing the CaWO4 / ZIF-67 composite material are: Ca(NO3)2·4H2O, Na2WO4·2H2O, Co(NO3)2·6H2O, CTAB, C4H6N2 and Fe3O4; The preparation method of the CaWO4 / ZIF-67 composite material specifically comprises the following steps: S1, weighing Ca(NO3)2·4H2O and dissolving it in ethylene glycol to form a first solution, weighing Na2WO4·2H2O and dissolving it in deionized water to form a second solution, then pouring the second solution into the first solution, stirring and mixing, to form a mixture; S2, subjecting the mixture obtained in step S1 to a hydrothermal reaction, cooling the mixture to room temperature after the reaction is completed to obtain a white precipitate, washing the obtained white precipitate, drying it, taking it out and grinding it to obtain CaWO4; S3, add CTAB and Co(NO3)2·6H2O to deionized water, and perform ultrasonic treatment to form a uniform solution A, add C4H6N2 and Fe3O4 to anhydrous ethanol to obtain a solution B, and slowly pour the solution A into the solution B, mix well, and form a mixed solution; S4, adding the CaWO4 prepared in step S2 to the mixed solution obtained in step S3, mixing by ultrasonication, drying to obtain a composite material precursor, and then calcining the composite material precursor to obtain a CaWO4 / ZIF-67 composite material.

2. A high-efficiency sewage treatment agent according to claim 1, characterized in that: In step S1, the molar ratio of Ca(NO3)2·4H2O to Na2WO4·2H2O is 1:1, the dosage ratio of Ca(NO3)2·4H2O to ethylene glycol is 0.1 g:7 mL, the dosage ratio of Na2WO4·2H2O to deionized water is 0.1 g:15 mL, the stirring is magnetic stirring, stirring at a speed of 180-300 rpm, and the temperature is set to 70 °C.

3. A high-efficiency sewage treatment agent according to claim 1, characterized in that: In step S2, the hydrothermal reaction is carried out in a 100 mL polytetrafluoroethylene-lined reactor, the temperature is set to 180°C, and the reaction time is set to 24 h.

4. The high-efficiency sewage treatment agent according to claim 1, characterized in that: In step S3, the dosage ratio of CATB, Co(NO3)2·6H2O and deionized water is 1 mg:0.15 g:2.5 mL, the dosage ratio of C4H6N2, Fe3O4 and anhydrous ethanol is 1 g:0.5 g:10 mL, and the volume ratio of solution A to solution B is 1:

12.

5. The high-efficiency sewage treatment agent according to claim 1, characterized in that: In step S4, the dosage ratio of CaWO4 to the mixed solution is 0.1-0.5 g:25 mL.

6. A high-efficiency sewage treatment agent according to claim 1, characterized in that: In step S4, the calcination is carried out by uniformly heating to 400°C at a heating rate of 5°C / min at room temperature, and maintaining the calcination at this temperature for 2-4 hours.

7. A method for preparing a high-efficiency sewage treatment agent according to any one of claims 1 to 6, characterized in that: The specific steps include: Y1, weigh Al2(SO4)3 and Fe2O3 by weight, dissolve them in deionized water, and stir at 200-500 rpm to form a mixed solution; Y2, weighing CaWO4 / ZIF-67 composite material and NaHSO3 by weight, adding them to the mixed solution obtained in step Y1, and mixing them at 70-90°C and 200 rpm with magnetic stirring to form a suspension; Y3. Add Na2SiO3 and MnO2 to the suspension obtained in step Y2, stir and mix at 300 rpm, let stand for 30-60 min, then centrifuge and dry to obtain a high-efficiency sewage treatment agent.

Citation Information

Patent Citations

  • Preparation method of WO3 / ZnWO4 composite micro-nano fiber and product of WO3 / ZnWO4 composite micro-nano fiber

    CN107299417A

  • Preparation method of ZIF-67@FP composite adsorbing material and application thereof to separation and enrichment of cadmium-containing high salinity wastewater

    CN107486165A

  • Magnetic metal-organic framework material and preparation method thereof

    CN108114697A

  • Core-shell structure Fe3O4@ZIF-67 material as well as preparation and application thereof

    CN110560003A

  • ZIF packaged polyoxometallate host-guest composite material as well as preparation method and application thereof

    CN116273095A